2019
DOI: 10.1038/s41598-019-41321-y
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling a Scaling and Universal Behavior for the Magnetocaloric Effect in Cubic Crystal Structures: A Monte Carlo Simulation

Abstract: The magnetocaloric effect and the universal character for the magnetic entropy change regarding the cubic crystal structures (SC, BCC, FCC) were investigated, in a qualitative way, using Monte Carlo simulations. A classical Heisenberg Hamiltonian with nearest neighbors, and next nearest neighbors interactions was implemented. In order to compute the critical temperature of the system depending on the coordination number, it was calculated the dependence of the magnetization and magnetic susceptibility as a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Rh and also with tunable magnetic properties according to exact composition [21]. For example, Huang et al [13] reported that the meltspun Al 0.44 Cr 0.25 MnFeCo 0.25 Ni 0.2 alloy with the BCC structure has ∆S M of 0.458 Jkg −1 K −1 , and RCP of 27 Jkg −1 at a magnetic field of ∼0.82 T. Recent studies suggest that ∆S M is larger for HEAs in the BCC structure in comparison with that in the FCC structure due to the larger coordination number of the FCC structure [22]. For example, Na et al [23] studied the structural and magnetocaloric properties of the AlCrFeCoNi HEA.…”
Section: Introductionmentioning
confidence: 99%
“…Rh and also with tunable magnetic properties according to exact composition [21]. For example, Huang et al [13] reported that the meltspun Al 0.44 Cr 0.25 MnFeCo 0.25 Ni 0.2 alloy with the BCC structure has ∆S M of 0.458 Jkg −1 K −1 , and RCP of 27 Jkg −1 at a magnetic field of ∼0.82 T. Recent studies suggest that ∆S M is larger for HEAs in the BCC structure in comparison with that in the FCC structure due to the larger coordination number of the FCC structure [22]. For example, Na et al [23] studied the structural and magnetocaloric properties of the AlCrFeCoNi HEA.…”
Section: Introductionmentioning
confidence: 99%